Distinct Roles for Bruton's Tyrosine Kinase in B Cell Immune Synapse Formation - Roman-Garcia, Sara; Merino-Cortes, Sara V.; Gardeta, Sofia R.; de Bruijn, Marjolein J. W.; Hendriks, Rudi W.; Carrasco, Yolanda R. (Frontiers in Immunology, 2018)
Bruton’s tyrosine kinase (Btk) has a key role in the signaling pathways of receptors essential for the B lymphocyte response. Given its implication in B cell-related immunodeficiencies, leukemias/lymphomas and autoimmunity, Btk is studied intensely and is a target for therapy. Here we report distinct roles for Btk in antigen-triggered immune synapse (IS) formation of mouse primary B cells. Btk recruitment to the plasma membrane regulates the B cell ability to trigger IS formation as well as its appropriate molecular assembly; Btk shuttling/scaffold activities seem more relevant than the kinase function on that. Btk-kinase activity controls antigen accumulation at the IS through the PLCg2/Ca2+ axis. Impaired Btk membrane-recruitment or kinase function likewise alters antigen-triggered microtubule-organizing center (MTOC) polarization to the IS, B cell activation and proliferation. Data also show that, for B cell function, IS architecture is as important as the quantity of antigen that accumulates at the synapse.